Models of neural networks III association, generalization, and representation - Domany, E. (Eytan) 1947-; Hemmen, J.L. van (Jan Leonard) 1947-; Schulten, K. (Klaus) (Physics of neural networks, 1996)
Presents a collection of articles by leading researchers in neural networks. This work focuses on data storage and retrieval, and the recognition of handwriting.